THE EFFECT OF SUSTAINABILITY REPORTING ON FINANCIAL PERFORMANCE DURING THE COVID-19 PANDEMIC - Oviwasat Nawacatur; Irwan Trinugroho (Universitas Sarjanawiyata Tamansiswa, 2023)
The study aims to examine the effect of perfomance disclosure and sustainability report, including economic perfomance and social performance on the financial perfomance of companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period, which during this time span was the early period of the Covid-19 pandemic. The independent variable in this study is the sustainability report (X), while the dependent variable in this study is financial performance (Y1) and market performance (Y2), the control variable is represented by financial leverage, total assets, and audi quality which is one of the fundamental information for market participants. The sample used in this study is a company selected based on the purposive sampling method. The analytical method used in this study is multiple linear regression test, by testing the hypotesis T test